Some "Biological Nonsenses" from the position of the karyogamic theory of carcinogenesis - Gogichadze GDK; Gedenidze SG; Gogichadze TG (Annals of Cytology and Pathology - Peertechz Publications, 2020)
Malignant transformation of the normal somatic cells into tumorous ones can be assisted by the very difference in their nature agents and factors: penetrating radiation of different nature, numerous chemical substances, some oncogenic and infectious viruses, some toxins, pharmacological agents, some kind of irritation and some non-carcinogenic substance. Probably, the above-numerated agents and factors start up some a common mechanism of the conversion of normal cells into transformed state. As shown, carcinogenic potencies of some fatty acids, carbohydrates, and even distilled water and saline may be explained from the standpoint of karyogamic theory of carcinogenesis. All above-mentioned substances may induce perforations of different volume of plasma membranes of somatic cells. This may premise for cells' fusion process. In result of perforations, total negative charge of plasma membranes decrease, and the somatic cells acquire the capability of contacts with each other, which upon coincidence of the perforated sites of these organoids, may serve as a prerequisite to fusion process.